Impact of additional risk factors on the incidence of preterm delivery among pregnant women diagnosed with short cervix - Taiki Samejima; Takeshi Nagamatsu; Takayuki Iriyama; Toshio Nakayama; Takahiro Seyama; Seisuke Sayama; Keiichi Kumasawa; Atsushi Komatsu; Kei Kawana; Yutaka Osuga; Tomoyuki Fujii (Elsevier, 2020)
Objective: Additional risk factors for preterm delivery in pregnant women with cervical shortening are not fully understood; however, mid-trimester cervical shortening is accepted as a risk factor for preterm delivery. This study aimed to identify risk factors associated with subsequent preterm delivery among patients with short cervix detected after late mid-trimester. Materials and methods: This was a retrospective study of medical data from a single perinatal tertiary facility. We identified 134 asymptomatic women with singleton pregnancies where cervical shortening (≤25 mm) was detected during routine universal screening at 22-33 weeks. Statistical analyses were conducted to identify causal relationships between the incidence of preterm delivery and known risk factors for preterm delivery. Results: Incidence of preterm delivery was 27.6% (37/134) and preterm premature rupture of membrane was preceded in 46.0% (17/37) of the women with preterm delivery. Using logistic regression analysis, we identified uterine contractions [aOR 4.25, 95% confidence intervals (CI):1.68-12.1] and increased C-reactive protein (CRP) and increased white blood cell (WBC) in blood test (CRP: aOR 3.45, 95% CI:1.50-9.71; WBC: aOR 1.28, 95% CI: 1.08-1.55) as risk factors which significantly increased the risk of preterm delivery among women diagnosed with short cervix. Preterm delivery occurred in 91% of women positive for both uterine contractions and CRP >0.5 mg/dl. Conclusions: Uterine contraction and elevated CRP were additional risk factors for preterm delivery among women with short cervix. These results might be clinically useful to evaluate subsequent risk for preterm delivery in asymptomatic pregnant women presenting with short cervix in mid-pregnancy. Keywords: Preterm labor, Cervical length, Inflammation, Pregnancy